Extracorporeal Shockwave Therapy Modulates the Expressions of Proinflammatory Cytokines IL33 and IL17A, and Their Receptors ST2 and IL17RA, within the Articular Cartilage in Early Avascular Necrosis of the Femoral Head in a Rat Model - Jai-Hong Cheng; Shun-Wun Jhan; Chieh-Cheng Hsu; Hung-Wen Chiu; Shan-Ling Hsu (Mediators of Inflammation)
Avascular necrosis (AVN) of the femoral head (AVNFH) is a disease caused by injury to the blood supply of the femoral head, resulting in a collapse with osteonecrosis and damage to the articular cartilage. Extracorporeal shockwave therapy (ESWT) has been demonstrated to improve AVNFH owing to its anti-inflammation activity, angiogenesis effect, and tissue regeneration in clinical treatment. However, there are still so many pieces of the jigsaw that need to be fit into place in order to ascertain the mechanism of ESWT for the treatment of AVNFH. The study demonstrated that ESWT significantly protected the trabecular bone volume fraction BV/TV (P<0.01) and the trabecular thickness (P<0.001), while in contrast, the trabecular number and trabecular separation were not significantly different after treatment as compared with AVNFH. ESWT protected the articular cartilage in animal model of AVNFH. The levels of IL1-β and IL33 were significantly induced in the AVNFH group (P<0.001) as compared with Sham and ESWT groups and reduced in ESWT group (P<0.001) as compared with AVNFH group. In addition, the expression of the receptor of IL33, ST2, was reduced in AVNFH and induced after ESWT (P<0.001). The expression of IL17A was induced in the AVNFH group (P<0.001) and reduced in the ESWT group (P<0.001). Further, the expression of the receptor of IL17A, IL17RA, was reduced in the AVNFH group (P<0.001) and improved to a normal level in the ESWT group as compared with Sham group (P<0.001). Taken together, the results of the study indicated that ESWT modulated the expression of IL1-β, pro-inflammatory cytokines IL33 and IL17A, and their receptors ST2 and IL17RA, to protect against loss of the extracellular matrix in the articular cartilage of early AVNFH.